THE NURSE IN THE CONTEXT OF TECHNICAL-LEVEL EDUCATION: TEACHING CHALLENGES DURING THE COVID-19 PANDEMIC - Rodrigues Vitorio Pacheco, Dirce; Ferreira de Souza, Marly (Revista Gênero e Interdisciplinaridade, 2022)
Introduction: Teacher training encompasses a series of factors and circumstances of specific and pedagogical knowledge. In this process, teaching-learning is linked to the development of knowledge, skills and attitudes. In technical education, there are active methodologies for health courses, especially in nursing, however, several factors have hampered the quality of this education. In this line of thought, this study was developed from the existing problem of the various difficulties that the teaching nurse faces in the classroom at a technical level, from the perspective of the predisposing adversities for such circumstances, aiming to identify in the literature, scientific evidence about of the main challenges faced by nurses in teaching during the Covid-19 pandemic, in technical education. Methodology: This is an integrative literature review, of a descriptive-exploratory nature, carried out from bibliographic searches in the scientific databases: SCIELO, LILACS and BDENF. Results and Discussions: The main challenges for teaching encompass different circumstances, being them at a social and economic level, where the professional is not always supported by all the necessary resources to promote quality teaching, as well as the behavior and interest of students. , which for the most part does not play its current role. Conclusion: It was evidenced that the traditional teaching model does not always attract the attention and interest of students, making it necessary to implement new teaching practices that involve recreational and dynamic activities, especially with regard to remote online classes in periods of isolation.